CD44-Targeted Nanocarrier for Cancer Therapy - Kesharwani, Prashant; Chadar, Rahul; Sheikh, Afsana; Rizg, Waleed Y.; Safhi, Awaji Y (Frontiers in Pharmacology, 2022)
Cluster of differentiation 44 (CD44) is a cell surface glycoprotein overexpressed in varieties of solid tumors including pancreatic, breast, ovary, brain, and lung cancers. It is a multi-structural glycoprotein of cell surface which are majorly involved in cell proliferation, cell to cell interaction, cellular migration, inflammation, and generation of immune responses. Numerous studies focus on development of nanocarrier for the active targeting of CD44 receptor to improve efficacy of targeting chemotherapy and achieve precise chemotherapy by defining the release, uptake, and accumulation of therapeutic agents. CD44 receptor has selective binding affinity towards hyaluronic and chondroitin sulfate (CS). Taking into consideration, this review focussed on role of CD44 in cancer and its therapy using several nanocarriers such as polymeric/non-polymeric nanoparticles, dendrimer, micelles, Carbon nanotubes, nanogels, nanoemulsions etc, for targeted delivery of several chemotherapeutic molecules and genes. This review also illuminates the role of hyaluronic acid (HA) in cancer therapy, interaction of HA with CD44 and various approaches to target CD44 overexpressed neoplastic cells.